2013
DOI: 10.1159/000355284
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathology of Extracranial Ectopic and Metastatic Meningiomas

Abstract: Introduction: Extracranial meningiomas may infrequently be encountered as ectopic or metastatic tumors. Their rarity and unique cytomorphology often pose significant diagnostic dilemmas. The aim of this study was to report our experience with a series of ectopic and metastatic meningiomas, characterizing their cytomorphology with histological correlation. Materials and Methods: A retrospective analysis involving 13 patients with cytological preparations from extracranial meningiomas was performed. Cytology cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…[822] However, studies have stated that the occurrence of these features in benign lesions is very less as compared to PTC. [23] In our study also, we observed the same reasons for false positive cases. Figures 2a and c show nuclear grooves on the cytology of cases, which were found to be adenomatous goiter and Hashimoto's thyroiditis on histopathology, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…[822] However, studies have stated that the occurrence of these features in benign lesions is very less as compared to PTC. [23] In our study also, we observed the same reasons for false positive cases. Figures 2a and c show nuclear grooves on the cytology of cases, which were found to be adenomatous goiter and Hashimoto's thyroiditis on histopathology, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…There is evidence in the literature that the characteristic features of PTC like nuclear grooves, nuclear pseudo-inclusions and many more features can be seen in benign conditions of thyroid like adenomatous goiter, Hashimoto's thyroiditis, nodular goiter, follicular neoplasm, etc [18,47]. However, studies have stated that occurrence of these features in benign lesions is very less as compared to PTC [48]. Hence, awareness of pathologists in this context and strict adherence to adequacy criterion can reduce the false positive rate.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathology and immunohistochemistry are confirmatory. Meningiomas are strongly immunoreactive to EMA, pancytokeratin and Vimentin [9].…”
Section: Discussionmentioning
confidence: 99%